Interaction of Aqueous Cu2+ Ions with Granules of Crushed Concrete - F. Ali, Alyaa; T. Abd Ali, Ziad (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
The sorption of Cu2+ ions from synthetic wastewater using crushed concrete demolition waste (CCDW) which collected from a demolition site was investigated in a batch sorption system. Factors inﬂuencing on sorption process such as shaking time (0-300min), the initial concentration of contaminant (100-750mg/L), shaking speed (0-250 rpm), and adsorbent dosage (0.05-3 g/ml) have been studied. Batch experiments confirmed that the best values of these parameters were (180 min, 100 mg/l, 250 rpm, 0.7 g CCDW/100 ml) respectively where the achieved removal efficiency is equal to 100%. Sorption data were described using four isotherm models (Langmuir, Freundlich, Redlich-Peterson, and Radke-Prausnitz). Results proved that the pure adsorption and precipitation are the main mechanisms for removal of copper ions from aqueous solution onto CCDW and sorption data can be represented by Langmuir and Radke-Prausnitz model. The copper ion was successfully removed from aqueous solution during batch experiments using CCDW in the particle size range 2–1 mm. Scanning electron microscopy detected that the removal of Cu2+ was found to arise from surface precipitation.